Altered Resting State Functional Activity and Microstructure of the White Matter in Migraine With Aura - Faragó, Péter; Tóth, Eszter; Kocsis, Krisztián; Kincses, Bálint; Veréb, Dániel; Király, András; Bozsik, Bence; Tajti, János; Párdutz, Árpád; Szok, Délia; Vécsei, László; Szabó, Nikoletta; et al. (Frontiers in Neurology, 2019)
Introduction: Brain structure and function was reported altered in migraine. Importantly our earlier results showed that white matter diffusion abnormalities and resting state functional activity was differentially affected in the two subtypes of the diseases, migraine with and without aura. Resting fluctuation of the BOLD signal in the white matter was reported recently. The question arising if the white matter activity, that is strongly coupled with grey matter activity is also perturbed differentially in the two subtypes of the disease and if so, whether it was related to the microstructural alterations of the white matter. Methods: Resting state fMRI, 60 directional DTI images and high-resolution T1 images were obtained from 51 migraine patients and 32 healthy volunteers. The images were pre-processed and the white matter was extracted. Independent component analysis was performed to obtain white matter functional networks. The differential expression of the white matter functional networks in the two subtypes of the disease was investigated with dural-regression approach. The Fourier spectrum of the resting fMRI fluctuations were compared between groups. Woxel-wise correlation was calculated between the resting state functional activity fluctuations and white matter microstructural measures. Results: Three white matter networks were identified that were differentially expressed in migraine with and without aura. Migraineurs with aura showed increased functional connectivity and amplitude of BOLD fluctutation. Fractional anisotropy and radial diffusivity showed strong correlation with the expression of the frontal white matter network in patients with aura. Discussion: Our study is the first to describe changes in white matter resting state functional activity in migraine with aura, that correlates with the underlying microstructure. Functional and structural differences between disease subtypes suggest at least partially different pathomechanism, which may necessitate handling of these subtypes as separate entities in further studies.